Magnetically stimulated transient creep processes in a heterogeneous aluminum alloy with ferromagnetic inclusions - Vladimir Nikolaev; Mounir Friha; Arkady A. Skvortsov; Danila Pshonkin; Aleksandr Abramov; Polina Kuznetsova; Alexandr Kazak (Scientific Reports)
Abstract This study analyzes the creep processes of a heterogeneous aluminum alloy containing ferromagnetic inclusions with an average size of 3–5 μm, and the influence of preliminary magnetic exposure (in a constant magnetic field (MF) with induction B < 0.75 T) on these processes. Experimental investigations were carried out to determine the characteristic times of the transient stages of short-term creep, which do not exceed approximately 25 ms. We analyzed the transient deformation behavior of the aluminum-based alloy and consequently determined the elastic moduli of the material, along with the influence of preliminary magnetic exposure on them. It was established that the MF has the most pronounced effect on the “long-term” elastic modulus H (defined as the ratio of stress to the relative strain of the material after sustained application of a constant load). We propose that the observed linear decrease in H with increasing B is associated with the magnetostriction of the inclusions during preliminary magnetic exposure. An increase in magnetic induction enhances local stresses at the matrix–inclusion interfaces, which in turn leads to a rise in dislocation density. These microstructural changes influence the subsequent deformation behavior, including both transient responses under loading and stress relaxation during unloading. We conclude that the elastic modulus H is the most sensitive parameter to the influence of magnetic fields, indicating a significant impact of external MF on the creep dynamics of the structurally heterogeneous aluminum alloy under investigation.